Green synthesis and functional evaluation of zinc oxide nanoparticles from red dragon fruit peel - Rathi, Devi Nair Gunasegavan; Saad, Norazalina; Mohd Esa, Norhaizan; Abd Rashed, Aswir; Md Noh, Mohd Fairulnizal; Che Abdullah, Che Azurahanim (Nature Research, 2025)
Using red dragon fruit peel extract (RDPE) as a biogenic reducing and stabilizing agent, this paper presents an inexpensive, eco-friendly and simple biogenic synthesis of zinc oxide nanoparticles (ZnONPs). These biogenic materials are non-hazardous, environmentally friendly, and incur minimal costs compared to chemical approaches. The successful biosynthesis of ZnONPs was confirmed using several characterization tests, including UV-Vis spectroscopy, particle size analysis, zeta potential analysis, Fourier transform infrared spectroscopy, thermogravimetric analysis, X-ray diffraction spectroscopy, Field-emission scanning electron microscopy and Energy dispersive X-ray spectroscopy. In addition, a Taguchi experimental design was employed to optimize the synthesis conditions, resulting in nine formulations that incorporated the effects of two zinc salt precursors (acetate and nitrate). Among these, acetate-derived ZnONPs produced the desired hydrodynamic size (203.97 ± 1.53 nm) and best colloidal stability (zeta potential: − 29.4 ± 0.89 mV) with formulation AR7. The hexagonal wurtzite phase with a crystallite size of 18.00 ± 5.32 nm was verified by X-ray diffraction. FTIR spectra showed the presence of phytochemical functional groups in charge of capping and reduction. FESEM revealed unique flower-like morphology, with an average particle size of 45.85 ± 4.64 nm, proving the efficacy of AR7 as the optimal formulation. The antimicrobial activity tests revealed minimum inhibitory concentration values of 2.50–5.00 µg/mL against Escherichia coli, Staphylococcus aureus, and Candida albicans; while an IC50 of 405 µg/mL was obtained with the cytotoxicity test on 3T3-L1 cells after 24 h of incubation. These results imply that the optimal formulation of AR7, mediated from RDPE, presents excellent prospects in reducing environmental wastage for widespread biomedical applications.